2010
DOI: 10.1186/1471-2458-10-78
|View full text |Cite
|
Sign up to set email alerts
|

The role of social support and social networks in smoking behavior among middle and older aged people in rural areas of South Korea: A cross-sectional study

Abstract: BackgroundAlthough the number of studies on anti-smoking interventions has increased, studies focused on identifying social contextual factors in rural areas are scarce. The purpose of this study was to explore the role of social support and social networks in smoking behavior among middle and older aged people living in rural areas of South Korea.MethodsThe study employed a cross-sectional design. Participants included 1,057 adults, with a mean age of 60.7 years, residing in rural areas. Information on partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 50 publications
(61 reference statements)
2
36
0
Order By: Relevance
“…In a US Study, Samuel et al also reported that emotional social support and neighborhood social cohesion were generally linked to lower smoking rates [7]. However, in the same paper, the authors pointed out that social support and social cohesion may be associated with higher smoking rate in groups with high rates of smoking, which is in line with previous research [25][26][27] and the current study. Past research has shown that the greater the social network size, the more likely a person is to smoke, especially in Asian cultures where collectivism is valued [28].…”
Section: Tobacco Alcohol Use and Dietsupporting
confidence: 90%
“…In a US Study, Samuel et al also reported that emotional social support and neighborhood social cohesion were generally linked to lower smoking rates [7]. However, in the same paper, the authors pointed out that social support and social cohesion may be associated with higher smoking rate in groups with high rates of smoking, which is in line with previous research [25][26][27] and the current study. Past research has shown that the greater the social network size, the more likely a person is to smoke, especially in Asian cultures where collectivism is valued [28].…”
Section: Tobacco Alcohol Use and Dietsupporting
confidence: 90%
“…However, social support (Yun, Kang, Lim, Oh, & Son, 2010) and social cohesion (Chuang & Chuang, 2008; Li et al, 2012) may be associated with higher smoking rates in groups with high rates of smoking. Emotional social support (Weyers et al, 2010) and neighborhood social cohesion (Cleland et al, 2010; Cradock, Kawachi, Colditz, Gortmaker, & Buka, 2009; Pabayo, Belsky, Gauvin, & Curtis, 2010; Shelton et al, 2011; Utter, Denny, Robinson, Ameratunga, & Milfont, 2011; Echeverria, Diez-Roux, Shea, Borrell, & Jackson, 2008) are often associated with greater, and loneliness with less (Hawkley, Thisted, & Cacioppo, 2009; Shankar et al, 2011), physical activity, although associations are inconsistent for social support (Debnam, Holt, Clark, Roth, & Southward, 2012; Poortinga, 2006b) loneliness (Lauder et al, 2006) and social cohesion (Ball et al, 2010; Veitch et al, 2012) in similar large, diverse samples.…”
Section: Introduction1mentioning
confidence: 99%
“…Jeffery & Rick, 2002), at simple indices of social network indicators (e.g. Yun et al, 2010) or at isolated indicators of the social network (e.g. Voorhees & Young, 2003).…”
Section: Introductionmentioning
confidence: 99%